APPLICATION OF ENDOPHYTIC BACTERIUM BIOFERTILIZER IN TOMATOES HYDROPONIC SYSTEM - Imas Komalasari; Mieke Rochimi Setiawati; Ridha Hudaya (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2018)
The study was aimed at determining the role of endophytic bacteria biofertilizers as the substitutes for the use of inorganic fertilizers for tomato hydroponic systems. The study was conducted in August-December 2017 at the Ciparanje Experimental Garden Greenhouse, Padjadjaran University. The experiment used a randomized block design (RBD) with 7 treatments and 8 replications. Treatment A: 100% inorganic nutrition + 0 biological fertilizer, B: 50% inorganic nutrition + 100% biological fertilizer, C: 75% inorganic nutrition + 100% biological fertilizer, D: 100% inorganic nutrition + 25% biological fertilizer, E: 100% inorganic nutrition + 50% biological fertilizer F: 100% inorganic nutrition + 75% biological fertilizer, G: 100% inorganic nutrition + 100% biological fertilizer. The results show that the application of biofertilizers by reducing the dose of inorganic fertilizer had no significant effect on the population of the leaf and the root on endophytic bacteria, N content and yield of tomato plants. Biofertilizers are able to increase the weight of tomato in the 50% treatment of inorganic nutrients + 100% biofertilizers (B) of 39.69% compared to the use of inorganic fertilizers only without the addition of biological fertilizers (A)APLIKASI PUPUK HAYATI BAKTERI ENDOFITIK PADA SISTEM HIDROPONIK TANAMAN TOMATPenelitian dilakukan untuk mengetahui peran pupuk hayati yang mengandung bakteri endofitik sebagai pensubstitusi penggunaan pupuk anorganik untuk tanaman tomat yang ditanam dengan sistem hidroponik. Penelitian dilakukan pada bulan Agustus-Desember 2017 di Rumah Kaca Kebun Percobaan Ciparanje, Universitas Padjadjaran. Percobaan menggunakan Rancangan Acak Kelompok (RAK) dengan 7 perlakuan dan 8 ulangan. Perlakuan A: 100% nutrisi anorganik + 0 pupuk hayati, B: 50% nutrisi anorganik + 100% pupuk hayati, C: 75%nutrisi anorganik + 100% pupuk hayati, D: 100% nutrisi anorganik + 25% pupuk hayati, E: 100% nutrisi anorganik + 50% pupuk hayati F: 100% nutrisi anorganik + 75% pupuk hayati,G: 100% nutrisi anorganik + 100% pupuk hayati. Hasil penelitian menunjukkan bahwa pemberian pupuk hayati dengan mengurangi dosis pupuk anorganik tidak berpengaruh nyata terhadap populasi bakteri endofitik daun dan akar, kandungan N dan hasil tanaman tomat. Pupuk hayati mampu meningkatkan bobot buah tomat pada perlakuan 50% nutrisi anorganik + 100% pupuk hayati (B) sebesar 39,69% dibandingkan hanya menggunakan pupuk anorganik tanpa penambahan pupuk hayati (A).